ANALISIS PENERAPAN AKAD MUDHARABAH PADA MASA KRISIS: STUDI KASUS PADA KJKS BMT UGT SIDOGIRI KECAMATAN GENTENG BANYUWANGI - Izza Aulia Yusvita Sari; Lucky Al Hafzy (Universitas KH. Mukhtar Syafaat, 2025)
This study aims to analyze the implementation mechanism of the mudharabah contract in microfinancing at KJKS BMT UGT Sidogiri, Genteng Branch, Banyuwangi during an economic crisis, identify the obstacles faced by both management and customers (mudharib). The method used is a descriptive qualitative approach with a case study design. The results show that amid the crisis, BMT Branch consistently maintained sharia principles through a profit-sharing system utilizing the revenue sharing method in accordance with DSN-MUI Fatwa No. 15/DSN-MUI/IX/2000. Despite facing an increased risk of default due to a decline in customers' turnover, the BMT implemented humane and riba-free financing rescue strategies, including business assistance, regular monitoring, and payment relaxation through restructuring and rescheduling policies decided through mutual consultation. The main obstacles identified include the difficulty of predicting business profits, weak financial reporting from customers, and the risk of moral hazard. Overall, mudharabah financing has proven to possess strong flexibility and resilience as an instrument for community economic empowerment in times of uncertainty. Keywords: Mudharabah, Crisis Period, BMT UGT Sidogiri